Ethnobotanical study of cowpea (Vigna unguiculata (L.) Walp.) in Senegal - Sarr, A.; Bodian, A.; Gueye, M.; Gueye, B.; Kanfany, G.; Diatta, C.; Bougma, L.A.; Diop, E.A.M.; Cisse, N.; Diouf, D.; Leclerc, C. (Springer, 2022)
Cowpea (Vigna unguiculata) plays a key role in family farming systems in Senegal. It makes an essential contribution to economic, nutritional and food security. Although it is crucial, little is known about how farmers classify the diversity of local varieties or about the social practices associated with them. The aim of this study is to characterize the farming practices associated with growing cowpea in Senegal. Surveys were conducted involving 335 rural farmers living in 37 villages, spread across seven regions that produce cowpea. An average of ten farmers were randomly selected in each village. The results reveal that cowpea is a key feature of cropping systems in the studied area. Our findings highlight the high diversity of local cowpea varieties with 59 local names inventoried. In 75% of cases, the name refers to the seed’s morphology or color. Cowpea production is more diverse in Diourbel and Louga and less diverse in the south. More than half the farmers (57%) acquired their cowpea seeds (early, semi-early and late maturity varieties) outside their village, either from markets, seed suppliers or NGOs. This new understanding of farmers’ expertize in the management of cowpea and its local variability will help to valorize local diversity in breeding programs.